Risk of Neurotoxicity with Multiple General Anaesthetics for Examination Under Anaesthesia in Paediatric Ophthalmology – A Cause for Concern? - O'Connell A; Stephenson KAJ; Flitcroft I (Clinical Ophthalmology, 2023)
Ann O’Connell, Kirk AJ Stephenson, Ian Flitcroft Ophthalmology Department, Children’s Health Ireland at Temple Street Hospital, Dublin, IrelandCorrespondence: Ann O’Connell, Children’s Health Ireland at Temple Street, Dublin, Ireland, Tel +353 1 8784200, Email annoconnell@rcsi.comPurpose: To evaluate the impact of clinical protocol change via active minimisation on the number of general anaesthetic (GA)/sedation episodes for diagnostic ophthalmic purposes at Children’s Health Ireland at Temple Street (CHI-TS), Dublin, Ireland, from 2016 to 2019, inclusive. Change was implemented following published cautionary principles in 2016 by the FDA regarding the potential neurotoxic risk from multiple GA exposure in children.Methods: Retrospective analysis of electronic operating theatre records was completed using procedure codes “Ophthalmological examination” and “Examination of fundi”. Available records for patients undergoing multiple examination under anaesthesia (EUA) procedures were assessed for demographics, indication. Comparison was made regarding overall EUA numbers and breakdown for each year, before and after the new departmental approach. From 2018 onward, a patient-centred, departmental strategy of active minimisation of EUA was adopted, using strategies of “training, technology and patience”. A literature review was conducted using online databases.Results: A total of 450 EUAs were performed over the 4 years investigated. In the former 2 years of the study period, prior to departmental policy change, EUAs represented 32% (304 of 948 total theatre episodes) of the ophthalmic theatre caseload. In the latter 2 years of this study period, this proportion fell to 19% (146 EUAs of 783 theatre episodes). Total theatre case numbers were comparable in both time periods. Eighteen children had multiple EUAs (ie, ≥ 2 EUAs, mean 6.5, SD 2.9) for life/sight threatening indications, totalling 116 EUAs (25.7%).Conclusion: A significant reduction in diagnostic EUA volume was accomplished resulting in reduced individual patient risk and increased capacity for surgical interventions. A detailed description of this methodology is included for the purposes of replication at comparable units. EUA will continue to play a crucial role in the management of life/sight threatening conditions but the application of a cautionary principle to reduce EUA, where possible, is appropriate to reduce potential for neurotoxicity.Keywords: paediatric ophthalmology, general anaesthesia, developmental neurotoxicity, ophthalmology, examination under anaesthesia, paediatric anaesthesiology